Esas Marías de la Literatura Costarricense (de la Virgen María a María Amoretti) - Jones León, Sonia (Universidad de Costa Rica. Campus Rodrigo Facio. Sitio web: https://www.ucr.ac.cr/ Teléfono: (506) 2511-4000. Correo de soporte: revistas@ucr.ac.cr, 2006)
Literary onomastics in Costa Rica has priviledged the name Mary from its very origin. Nonetheless, an evolution is emerging that could spell the end of the patriarchal paradigm, as far as this representation is concerned. This essay explores this "marian" imaginary to detect how the model has been constructed or deconstructed.